Impact of Perceived Convenience on Intention to Use Mobile Payments in Mediating Perceived Risk - Yumiad Fernando Richard,; Apolinaris S. Awotkay,; Florentina B. Parapaga, (Technium Social Sciences Journal, 2023)
This study analyzes the ease of use of consumer m-payment systems, besides that the risk factors for use are also studied related to the ease of use factor on the intention to use m-payment Gen Z to make payment transactions. The sample in this study was FEB Unmus management students with an average age of 22 years, totaling 165 respondents based on the returned questionnaire. The data were obtained using a research questionnaire adjusted to the variable construct. OLS regression was used to explain the influence of each factor. Given the increasingly advanced mobile technology and online payment instrument competition that continues to grow. The dominant consumer response to PEU2 items provides a clear picture, that privacy data security risks greatly interfere with the intention to use m-payment. Implicitly, mobile-based technology financial services are more compatible with the social behavior of Generation Z consumers, because for them using a mobile platform is a spontaneous solution. This study is certainly not perfect in explaining the role of the TAM model, further implications need to examine other factors such as subjective norms or lifestyle factors, and convenience factors because they use mobile devices anytime to make payments and m-payments quickly and easily. This means that Generation Z will use mobile payments more if they think that m-payment suits their lifestyle.